2022
DOI: 10.3390/catal12121518
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Oil Sands’ Mature Fine Tailings Using Advanced Wet Air Oxidation (WAO) and Wet Air Peroxide Oxidation (WAPO)

Abstract: Mature Fine Tailings (MFT) generated from oil sands processing represent a growing environmental issue, as settling of these tailings’ emulsion can take decades, increasing the risk of the toxic material’s leaching if left untreated. This study uses advanced wet air oxidation (WAO) and wet air peroxide oxidation (WAPO) to break down the MFT emulsions for faster settling. Three oxidation time intervals (5, 15, and 30 min) were investigated using compressed air and hydrogen peroxide in a pressurized vessel of 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…PFAS flame retardants probably originating from AFFF were also detected in oil sands processaffected water (OSPW), produced by the surface-mining activities as the oil sands industry in Alberta, Canada [39]. This finding emphasizes the increased risk of such toxic materials leaching into the groundwater if left untreated [40]. Another study conducted in the United States on different environmental media showed that the concentration of PFOS was the highest at 10 active US Air Force installations [41].…”
Section: Firefighting Stations Military Bases and Aviation Sitesmentioning
confidence: 97%
“…PFAS flame retardants probably originating from AFFF were also detected in oil sands processaffected water (OSPW), produced by the surface-mining activities as the oil sands industry in Alberta, Canada [39]. This finding emphasizes the increased risk of such toxic materials leaching into the groundwater if left untreated [40]. Another study conducted in the United States on different environmental media showed that the concentration of PFOS was the highest at 10 active US Air Force installations [41].…”
Section: Firefighting Stations Military Bases and Aviation Sitesmentioning
confidence: 97%